Effects of dual degree credit programs on retention and time to degree at the University of Wisconsin-L aCrosse - Rybaski, Joshua D. (My University, 2012)
The purpose of this study was to investigate the effects of enrollment in high school Advance Placement (AP) and/or Dual Enrollment (DE) programs on college retention and time to degree in a sample of 18,135 undergraduates between the years 1992 and 2002 at the University of Wisconsin-La Crosse (UW-L). The research compares the relationship between these variables for students who participated in these programs during high school with those students who did not participate. The results showed that AP/DE program enrollment is an effective strategy to help students persist and graduate more quickly.
Keywords: College -- school cooperation.; Dual enrollment.; College credits.; Advance placement programs (Education)